Magneto-Structural Properties of Ni2MnGa Ferromagnetic Shape Memory Alloy in Magnetic Fields - Takuo Sakon (Metals, 2013)
The purpose of this review was to investigate the correlation between magnetism and crystallographic structures as it relates to the martensite transformation of Ni2MnGa type alloys, which undergo martensite transformation below the Curie temperature. In particular, this paper focused on the physical properties in magnetic fields. Recent researches show that the martensite starting temperature (martensite transformation temperature) TM and the martensite to austenite transformation temperature (reverse martensite temperature) TR of Fe, Cu, or Co-doped Ni–Mn–Ga ferromagnetic shape memory alloys increase when compared to Ni2MnGa. These alloys show large field dependence of the martensite transformation temperature. The field dependence of the martensite transformation temperature, dTM/dB, is −4.2 K/T in Ni41Co9Mn32Ga18. The results of linear thermal strain and magnetization indicate that a magneto-structural transition occurred at TM and magnetic field influences the magnetism and also the crystal structures. Magnetocrystalline anisotropy was also determined and compared with other components of Ni2MnGa type shape memory alloys. In the last section, magnetic field-induced strain and magnetostriction was determined with some novel alloys.